Penggunaan model pembelajaran kooperatif tipe scramble untuk meningkatkan keterampilan menulis kalimat sederhana pada peserta didik kelas II sekolah dasar - Amanda Senja Karunia; Retno Winarni; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2020)
Abstract. The aim of this study to look out the effectiveness of Scramble in enhancement of second grade student of elementary school Karangasem III, Laweyan Surakarta in writing of simple sentence, scramble is a part of cooperative learning. The students arrange Scramble word which help to crate simple sentence. This study done some stages of action class study started from pre-test until third cycle. The collecting data that used on this study are intervieuw with teacher and students, observation, and documenting which the writer got by doing writing test. There are some result wrote thet 48,5 for pre-test, 63,4 for cycle I, 70,85 for cycle II and cycle III is 86,5. I conclusion, Scramble is effective to enhancement students writing skill, simple sentence.Keywords: Scramble, simple sentence, elementary school